ASOSIASI JENIS Ceriops tagal (TENGAR) DI HUTAN MANGROVE KAWASAN BEDUL TAMAN NASIONAL ALAS PURWO BANYUWANGI JAWA TIMUR - , PARULIAN SITUMORANG, Dr. Erny Poedjirahajoe, M.P. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Bedul mangrove area located around Segara Anak river is a mangrove forest located in Alas Purwo National Park. The last few years see the species of Ceriops tagal is very dominant at the level of seedling and saplings in some mangrove forest areas around Segara Anak. One way to maintain the stability of mangrove forest ecosystem is to find associative information between two different species living in one area. This research titled âAssociative Species Ceriops tagal in Bedul Mangrove areas in Alas Purwo National Park is one of the real action to preserve the stability of the ecosystem in this region This study aims to determine the importance value index (IVI) of vegetation and the association of Ceriops tagal with other species living in the Bedul mangrove area of the Alas Purwo National Park. The method used in this research is the systematic sampling with quadratic forms. Squared sampling size used was 10x10 feet to the level of the tree, 5x5 m for sapling level, and 2x2 for Seedlings. Distances between plots used is 50 meters. IS is used by 1.3% with the plot number 39. Calculated from data obtained Importance value index of each type. To determine the association of Ceriops tagal, the research uses 2x2 contingency tables. Chi-square test is used to measure the value of the deviation. The results showed that Ceriops tagal dominates Bedul mangrove areas which is indicated by the highest IVI value for seedlings, saplings and trees. At the seedling level, the association of Ceriops tagal with other species is unnoticably positive, but more noticably negative. At the level of sapling, Ceriops tagal is not positively associated with other species, but the contrary is negatively associated with other species at tree level. A positive associations indicate that species can live together, while negative associations indicate that species others cannot live together.